Ta’thīru Wabā’i Kūfīd 19 ‘alā Fahmi Ta‘līm al-Lughah al-‘Arabiyyah li-Ṭullāb aṣ-Ṣaff as-Sābi‘ fī al-Madrasah ath-Thānawiyyah al-Ahliyah "Miftāḥ al-‘Ulūm" Kepenuhan Raya Riau - Serli Sururom Mahsunah; Isniyatun Niswah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
Pandemic covid 19 has changed various aspect of human life today. This requires all elements of education to adapt and continue the rest of the semester online. The purpose of this study was to determine whether  there was an influence on the undestanding og Arabic learning in students of first class at Miftahul Ulum Kepenuhan Raya Junior High School. This research uses Quantitative method. The result  of the research were the influence of the Pandemic covid 19 on understanding Arabic learning. This happened because online learning  was not optimal. Which made students have difficulty understanding Arabic learning. Miftahul Ulum Kepenuhan Raya Junior High School is an educational institution that is located in a difficult network area, so learning is only through whatssup group. Or students come to the teacherâ€™s home to take on assigment. So these students do not get optimal learning from the teacher.